Critical reflections in the anthropocene
1 online resource.
Keywords: "Incorporating the intellectual history of disciplines from across the humanities, including environmental anthropology, philosophy, ethics, literature, history, science and technology studies, this volume provides a select orientation to the experience of nature from the ancient world to the Anthropocene. Taking its momentum from the emerging environmental humanities, this collection integrates Western, Indigenous, postcolonial, feminist and eco-spiritual perspectives that address pressing environmental concerns and reimagine the place of humans within the natural world. Across thirteen chapters, the contributors discuss the blending of environmental concerns with political and moral questions and encourage collaborative methods across disciplines to address dialectical tensions between culture and nature. They draw on a wide range of critical perspectives, provide a historical framework and speak to global environmental pressures from multiple standpoints. Written to appeal to a broad range of readers across the environmental humanities, this edited book will be particularly useful to academics, scholars and researchers in philosophy, anthropology, literature, history and critical theory"--